(untitled) (Journal of Rashid Latif Medical College, 2022)
Background: Mutations in different genes like EGFR, ALK and BRAF are the sources of non-small cell lung cancer. Mutation of ALK occurs of small inversion on short arm of chromosome 2. The most commonly found EGFR mutations in patients with NSCLC are deletions in exon 29 or in exon 21. Common BRAF transversion mutations occur at exon 15. The missense mutations of BRAF have been detected in exon 11 and exon 15. Objective: The objective of study was to design new chemical compounds to block the targeted sites for receptor proteins present on cells surface, which control the growth or stop the proliferation of cancer cells. Methods: After screening large amount of data, we designed an in silico drug compound for lung cancer that block the mutations in EGFR, ALK and BRAF genes. Results: We suggested a novel compound (7-[2-(6-[4-(chloromethyl) piperazin-l-yl] oxan-3-yl amino) pyrimidin-5-yl]-octahydropyrano[2,3-c]pyridin-3-ol) to control mutations in EGFR, ALK and BRAF genes. Molecular formula of ligand compound C22H35C1N603 showed promising Lipinski rules of five values having Log P 0.58-1.86, molar refractivity 123.13 ± 0.3 cm3, H bond acceptors and donor 8 and 2 respectively. ALA, LYS, ARG were common interacting residues for EGFR, ALK genes and ALA, GLY were common for ALK, BRAF mutant genes and ligand complex interaction. Conclusion: ALA was common among all interactions that showed less side effects and long resistance against non-small cell lung cancer.